Plastic Bag Study - Gray, Michael (2018)
WAu! exhibition is composed of West Australian aboriginal artists and the works of internationally acknowledged photography artists based in Western Australia. The exhibition was carried out in co-operation with art center Warlayirti Artists Aboriginal Corporation in Balgo, Great Sandy Desert. The exhibition brings the antipodes to Finland whilst ironically presenting landscapes that provoke feelings of isolation in sparsely populated, harsh, deserted landscapes that Finnish viewers may identify with.